GAYA HIDUP INSTAGRAM DAN MINUM KOPI : KAJIAN REPRESENTASI DIRI, KONSUMERISME DAN HIBRIDITAS - Dhyani Widiyanti Hendranto (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2022)
The “Instagram lifestyle” is a lifestyle that represents eagerness to document a person’s daily life and then having it displayed on Instagram so that it can be known by the public at large. Popular content that is frequently displayed are moments of coffee drinking. Such coffee drinking moments which are displayed on Instagram are interesting subjects to be studied due to their connection to representations of a particular self-identity associated with a culture of consumerism. By using visual analysis in conjunction with literature research - especially those related to self-identity, consumerism, and post-colonialism culture - the study aims to see the relationship between coffee drinking activities, visual appearances on Instagram and their associated broader meanings. The results of the study show that there are attempts to form self-identities that are expressed in the virtual space through display of images accompanied by text and other supporting information (geographical tagging, captions, hashtags, etc.). Consumerism culture is also evident in the relationship between